Draft Annual Plan 2003-2004 Planning and Development Department Government of Bihar - Planning Commission (Planning Commission, 2003)
The state of Bihar was reorganized on 15th November, 2000. The reorganised state has an area of 94,163 sq.km, and a population of 82.88 million according to the 2001 Census . The population constitutes 8.07 percent of the total population of the country with only about 3 percent of the area thereof. As such the density of population is very high being 880 per sq.km. The decadal rate of growth of population during the decade 1991-2001 has been 28.43 percent.
Planning and Development Department Government of Bihar